The excretory urography in urologic specialty - Higginson, Alex (1957)
In the first twenty years of the century, the most sensational medical discovery has been that of excretory urography. The progress of this wonderful scan method has performed in all of medicine has been of incalculable proportions. Powerful weapon in the hands of the physician and general surgeon, has guided the diagnosis of conditions and diseases of the urinary system definitely and safely, thus extending the radius of the field, because there are countless cases that urogram discover and previously unnoticed, until the later stages when the clinical manifestacionas was needed. But not only has fueled urography urologic diagnosis in General Medicine and Surgery, in the art she has created a revolution, which has imposed new theories; has transformed the evolution of many morbid pictures and has arrested many unhappy inherent complications instrumental exploration indispensable before their appearance; has focused on the best surgical treatment of diseases such as tuberculosis whose management has been totally changed for her.